“Lanna Suite” for Flexible Ensemble - Panapongpaisarn, Adiwach (Rangsit Music Journal, 2023)
“Lanna suite” is a suite for the flexible ensemble band. The objectives are to create the compositions with Lanna folk melodies as materials for the flexible ensemble band and to disseminate the creative works in the form of flexible ensemble band. Music composition “Lanna suite” has the structure as a musical form of a suite consisting of 8 movements and is approximately 45 minutes in length. This composition uses Lanna folk melodies as materials combined with western composition techniques. Each of the eight sections in this composition has a different form and style depending on which song it is a part of. The accent of Lanna folk music is included into the primary melody, secondary melody, harmonics, patterns, and style in order to provide audience with a diversity of tastes while preserving the Lanna music's uniqueness. The composition has a total of 6 parts, along with 3 percussion parts. The percussion is an optional part, which can be chosen whether to play or not. If there are only few kinds of percussion instruments, which may not be complete as required by the song, it can still be possible to be played. However, if playing percussion style, it will make the song more vivid.